Personal Data Privacy in Social Media Platform: Governance, Ethics, an Regulatory Measures - Putri, Aprilia Dwi Santoso; Rina Arum (Westscience Press, 2025)
This study explores the complexities of personal data privacy in the context of social media platforms, and existing regulatory frameworks. Trough a multidisciplinary analytical approach, this study evaluates the relationshipbetween users privacy rights, data management practies by platforms, and corporate legal liability. As a theoretical frameworks, the theory of privacy rights, data governance theory, and the concept of platforms responbilityare used toanalyze this problem. The results of the study revealed that there is a significant gap between the business model of platforms that rely on data extraction and user privacy expectations. Also identified are the limitations of current regulations in the face of rapid technological dynamics. This research contributes to the literature by introducing an integrated privacy governance model, which seeks to accommodate the needs of a more adaptive regulatory stakeholder. These findings have important implications for policy development, industry practices, and improved digital literacy for users.